2022
DOI: 10.1002/gps.5803
|View full text |Cite
|
Sign up to set email alerts
|

‘Pushing back’: People newly diagnosed with dementia and their experiences of the Covid‐19 pandemic restrictions in England

Abstract: Background and Objectives: Research into people with dementia's experiences of the Covid-19 pandemic has tended to focus on vulnerabilities and negative outcomes, with the risk of reproducing a discourse in which people with dementia are positioned as passive. Informed by concepts positioning people with dementia as 'active social agents', we aimed to identify the pandemic-related challenges faced by people recently diagnosed with dementia and examine the ways in which they actively coped with, and adapted to,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Currently, qualitative research that specifically addresses this topic is scarce. The majority of studies examine, more broadly, the experiences of people with dementia and their carers during the pandemic and often note an increase in their use of digital technologies to engage with formal health and social care services 30–33 . Although Giebel et al 34 found that those unpaid carers and people with dementia that accessed digital support during this period reported these services to be of poorer quality and less effective than in‐person contact.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, qualitative research that specifically addresses this topic is scarce. The majority of studies examine, more broadly, the experiences of people with dementia and their carers during the pandemic and often note an increase in their use of digital technologies to engage with formal health and social care services 30–33 . Although Giebel et al 34 found that those unpaid carers and people with dementia that accessed digital support during this period reported these services to be of poorer quality and less effective than in‐person contact.…”
Section: Introductionmentioning
confidence: 99%
“…However, carers who used protective coping tended to talk about struggling personally, and some carers believed that hiding their feelings ultimately resulted in a situation in which hostile dyadic coping could occur. It is also useful to note that protective dyadic coping can reduce autonomy ( Seaman & Stone, 2017 ), exacerbating situational difficulties – for example when people with dementia actively employed their own individual coping strategies during the pandemic ( Dixon et al, 2022 ) or if carers misjudge their level of insight ( Marzanski, 2000 ). Using alternative styles of dyadic coping may help dyads maintain their quality of life, particularly when avenues for alternative emotional support are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Despite assertions that older adults, particularly those with cognitive impairment, are most vulnerable to the negative consequences of the pandemic, some evidence indicates that these individuals have been relatively unburdened or unaffected by the pandemic. 4,5 Viewing older adults with dementia as wholly burdened by the pandemic discounts their social citizenship 6 ; in other words, this frame detracts from acknowledging persons with dementia as equal citizens with rights, responsibilities, life purposes, and equal stakes in all aspects of private and public life. It also minimizes their ability or unique aptitude to seek, make, and convey meaning to maintain their quality of life despite dementia-related challenges.…”
mentioning
confidence: 99%
“…It also minimizes their ability or unique aptitude to seek, make, and convey meaning to maintain their quality of life despite dementia-related challenges. [5][6][7][8] As such, a social citizenship perspective provides a framework for more deeply and accurately weighing the roles, struggles, and coping abilities of persons with dementia and their family members during the COVID-19 pandemic. In addition to focusing solely on the negative impacts of the pandemic, most research to date has either focused on the person with dementia 9 or their family caregivers 10 but has not considered how the person with dementia and their family members are navigating the pandemic together.…”
mentioning
confidence: 99%
See 1 more Smart Citation